High-intensity, sport-specific cardiac rehabilitation training of a 22-year-old competitive cyclist after spontaneous coronary artery dissection. Issue 2 (3rd April 2018) - Weber, Nicholas; Weber, Adam; Carbone, Pasquale; Lawrence, Anne; Bilbrey, Tim; Schussler, Jeffrey M.; Adams, Jenny
ABSTRACT: A 22-year-old man with spontaneous coronary artery dissection wanted to assess the feasibility of returning to competitive cycling. He was referred to the cardiac rehabilitation (CR) program at Baylor Hamilton Heart and Vascular Hospital where staff designed a high-intensity, sport-specific training program that simulated the movements and forces associated with his goal activity. The program was symptom limited and enabled the patient to train earlier and at a higher intensity than is typically allowed in conventional CR programs. Daily exercise training was customized to match the physical demands of competitive cycling by using a road bike, an indoor bike power trainer, and an interactive indoor-cycling software program. This case illustrates how specialized CR training, tailored to a patient's specific goals, can aid in the return to vigorous physical activity. He completed the high-intensity exercise training program without adverse signs or symptoms.